2023
DOI: 10.1002/pca.3233
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase inhibitory activity of Sargassum fusiforme and characterisation of bioactive compounds

Abstract: IntroductionSargassum fusiforme (Harvey) Setchell, also known as Tot (in Korean) and Hijiki (in Japanese), is widely consumed in Korea, Japan, and China due to its health promoting properties. However, the bioactive component behind the biological activity is still unknown.ObjectivesWe aimed to optimise the extraction conditions for achieving maximum tyrosinase inhibition activity by using two sophisticated statistical tools, that is, response surface methodology (RSM) and artificial neural network (ANN). More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…The literature showed that phenolic acids lose certain fragments such as methyl (15 Da), hydroxyl (18 Da), and carboxyl (44 Da) during the collision, which helped in determining the compounds [ 3 ]. Compounds 1 – 14 have been tentatively identified in Sargassum fusiforme based on previously reported fragmentation behavior data ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 ]. Interestingly, 5-(3′,5′-Dihydroxyphenyl)-γ-valerolactone 3- O -glucuronide and coumaroylquinic acid were tentatively acknowledged for the first time in optimized MUAE SH extract.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature showed that phenolic acids lose certain fragments such as methyl (15 Da), hydroxyl (18 Da), and carboxyl (44 Da) during the collision, which helped in determining the compounds [ 3 ]. Compounds 1 – 14 have been tentatively identified in Sargassum fusiforme based on previously reported fragmentation behavior data ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 ]. Interestingly, 5-(3′,5′-Dihydroxyphenyl)-γ-valerolactone 3- O -glucuronide and coumaroylquinic acid were tentatively acknowledged for the first time in optimized MUAE SH extract.…”
Section: Resultsmentioning
confidence: 99%
“…The RSM–BBD model followed the methodology of Javed et al [ 15 ]. In short, four independent variables—time (X 1 ), temperature (X 2 ), ethanol concentration (X 3 ), and ultrasonic frequency (X 4 )—were checked against four experimental responses—total phenolic content (TPC, Y1), total flavonoid content (TFC, Y 2 ), 1-diphenyl-2-picrylhydrazyl (DPPH, Y 3 ), and 1-diphenyl-2-picrylhydrazyl (ABTS, Y 4 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular docking analysis showed that T-6 binds within the TYR cavity, forming hydrogen bonds with Val248, Ala323, Asn320, and Asn81; an ionic bond with Glu322; and engaging in pi-pi stacking interactions with Phe192. The active site of TYR is divided into three distinct regions [35]: a substrate-binding pocket with six histidine residues and a binuclear copper ion; a hydrophobic region comprising Val248, Phe264, Val283, and Pro284; and a solvent-exposed region with Glu189 and Arg268 [36][37][38]. Docking simulations indicated that T-6 may primarily interact with the first and second regions, consequently inhibiting enzyme activity.…”
Section: Discussionmentioning
confidence: 99%